Pengaruh Tunjangan Kinerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Pitumpanua Kabupaten Wajo - Asmanurhidayani Asmanurhidayani; Muh Justiawal; Jamal Qadar (Journal of Research and Development on Public Policy, 2024)
This research was conducted to determine the influence of performance allowances and employee performance. Apart from that, the general aim of this research is to analyze the magnitude of the influence of Performance Allowances on Employee Performance at the Pitumpanua District Office, Wajo Regency. This type of research uses a census type of research with a descriptive study method. The data collection techniques used are observation, documentation, questionnaires. The population of this research is employees at the Pitumpanua District office, Wajo Regency. This research uses descriptive data analysis techniques and inferential statistical data analysis techniques. The results of the research show that Performance Allowances and Employee Performance at the Pitumpanua District Office, Wajo Regency are included in the very good category. Apart from that, Performance Allowances have a positive and significant effect on employee performance at the Pitumpanua District Office, Wajo Regency.